Improving the quality of life of patients after treatment of osteochondrosis with the use of PRP-therapy - Badyin, I. Yu. (Journal of Education, Health and Sport, 2016)
There are a large number of methods for treating patients with cervical osteochondrosis. In the last decade, methods for the use of platelet-rich plasma (PRP) have been actively developed and are being introduced into practical medicine: to favor the engraftment of dental grafts, the healing of chronic trophic fistula of the extremities, and also for the targeted regeneration of damaged organs. Quality of life is an integral indicator of the totality of physical, psychological, emotional and social functioning characteristics of a person, consisting of subjective sensations and perception of one's health state. Assessment of QOL at the present stage takes an increasingly strong place in medicine, which reflects on the one hand, the emergence of new medical technologies that do not affect life expectancy, but significantly improve its quality, and on the other - increasing the patient's activity, increasing his role in choosing methods diagnosis, treatment and rehabilitation.Information on individual QOL contributes to more accurate planning and timely correction of the patient's treatment program, which is especially important in the treatment of long-term, chronic diseases, which include OX.The results of treatment of 120 patients with vertebrogenic pathology treated in the neurological department are presented. The obtained data illustrate the improvement of the indices of functional tests of the spine in the group of patients taking PRP-therapy.